Active lytic infection of human primary tonsillar B cells by KSHV and its noncytolytic control by activated CD4(+) T cells - Myoung, Jinjong (American Society for Clinical Investigation, 2011)

(untitled)
Kaposi sarcoma–associated herpesvirus (KSHV) is a B-lymphotropic virus whose primary site of replication is the oropharynx. KSHV can infect both T and B cells from primary tonsillar explant cultures. However, T cells do not support lytic replication, while B cells spontaneously produce substantial amounts of infectious virus. Here, we provide evidence for a mechanism by which activated T cells may promote or stabilize latency of KSHV infection in B cells. When mixed cultures of B cells and activated T cells were exposed to KSHV, little spontaneous virus production was observed. Removing T cells from the mix or treating the mixed culture with immune suppressants enhanced virus production. Adding back activated T cells to purified infected B cells efficiently suppressed KSHV production, primarily due to CD4(+) T cells. This suppressive activity required T cell activation and direct cell-cell contact, but not prior exposure to KSHV antigen. Suppression was not MHC restricted and did not result in killing of the target cell. We therefore propose that oropharyngeal T cells activated by a variety of stimuli can recognize ligands on infected target B cells, leading to signaling events that prevent spontaneous lytic activation and promote latent infection in this compartment.